Midkine-Notch2 Pathway Mediates Excessive Proliferation of Airway Smooth Muscle Cells in Chronic Obstructive Lung Disease - Deng, Tang; Huang, Qifeng; Lin, Kaiwen; Qian, Jin; Li, Qi; Li, Lihua; Xu, Shuangqin; Yun, Hongfang; Wang, Hangfei; Wu, Xinxin; Liu, Heng; Jin, Guiyun; et al. (Frontiers in Pharmacology, 2022)
Inflammation-induced proliferation of airway smooth muscle cells (ASMCs) and subsequent airway remodeling is a hallmark of chronic obstructive lung disease (COPD). The role of midkine (MK) in COPD is unclear. In this work, we explored the role of MK-Notch2 signaling in COPD by inhibiting the expression of MK using lentivirus shRNA in ASMCs in vitro and instillation of AAV9-MK in the airway of a COPD rat model in vivo. The results demonstrated that LPS decreased ASMC migration and proliferation, increased apoptosis and induced the expression of MK and Notch2 signaling molecules. Inhibition of MK exacerbated the changes in migration and proliferation but decreased the expression of MK and Notch2 signaling molecules. Rats treated with smoke fumigation and LPS showed features of COPD. The small airways of COPD rats were remodeled and lung function was significantly reduced. The expressions of TGF-, ICAM-1, HA, MMP-9, PC-III and LN in BALF and the expression of MK and Notch2 signaling molecules were significantly increased in the COPD rats compared with controls. Inhibition of MK reversed these changes. In conclusion, the MK-Notch2 pathway plays a key role in airway remodeling induced by ASMC proliferation. Targeting the MK-Notch2 pathway may be a new strategy for improving airway remodeling and preventing progressive decline of pulmonary function in COPD.